A Fine Rule From a Brutish World? An Experiment on Endogenous Punishment Institution and Trust - Huojun Sun; Maria Bigoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
By means of a laboratory experiment, we study the impact of the endogenous adoption of a collective punishment mechanism within a one-shot binary trust game. The experiment comprises three games. In the first one, the only equilibrium strategy is not to trust, and not to reciprocate. In the second we exogenously introduce a sanctioning rule that imposes on untrustworthy second-movers a penalty proportional to the number of those who reciprocate trust. This generates a second equilibrium where everybody trusts and reciprocates. In the third game, the collective punishment mechanism is adopted through majority-voting. In line with the theory, we find that the exogenous introduction of the punishment mechanism significantly increases trustworthiness, and to a lesser extent also trust. However, in the third game the majority of subjects vote against it: subjects seem to be unable to endogenously adopt an institution which, when exogenously imposed, proves to be efficiency enhancing.
Keywords: C72; C92; D72; 330